PELAKSANAAN TUGAS BELLBOY PADA FRONT OFFICE DEPARTMENT DI GRAND CENTRAL HOTEL PEKANBARU - Elvis Aulya Rahman; Andi M. Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aimed to implementation of bellboy duty of front office department at Grand Central Hotel Pekanbaru. This research aims : (1) to know show the bellboy duty implementation of front office department at Grand Central Hotel Pekanbaru, (2) to knows the resistance of bellboy duty implementation of front office department at Grand Central Hotel Pekanbaru. sample in this research are the Front Office Manager, Assistant Front Office Manager and Supervisor Front Office Department Grand Central Hotel Pekanbaru as an key informan. This research uses descriptive method to clarify the issues raised in this research. the results of this research indicate that based on the research results obtained on bellboy duty implementation of front office department at Grand Central Hotel Pekanbaru could be good enough. this is proved by the result of observation and interview was doing by researcher. constraints implementation of bellboy duty of front office department at Grand Central Hotel Pekanbaru: (1)Bellboy Grand Central Hotel Pekanbaru have to increase their ability on service quality. (2) Grand Central Hotel Pekanbaru still have problems to do the bellboy implementation, such as languange problems, rolling system and tools system. Keyword : Implementation, Bellboy, Front Office, Front Office Department, Front Office Manager, Assisten Front Office Manager, Job Description